Dinamika Kebudayaan dan Perubahan Sosial dalam Masyarakat Modern - San Mikael Sinambela; Mima Defliyanti Saragih; Joy Novi Yanti Lumbantobing; Murniwati Lase; M Iqbal (Lembag, 2025)
Culture refers to a set of fundamental assumptions that a group has developed and refined through its experiences in addressing external adaptations and internal integrations, which have proven effective enough to be considered valid. This study seeks to elucidate the reciprocal relationship between cultural values and the dynamics of modern society, including their impact on thought patterns, behaviors, and social structures within the context of globalization. Employing a literature review approach, this research examines existing studies on cultural dynamics and social change in modern society to gain a comprehensive understanding of the cultural and social shifts occurring over time.